Development of Learning Media Based on Electrical Control Techniques Simulator to Improve Learning Achievement (Studies on Electrical Power Installation Engineering Subjects for Class XI Students at Rejang Lebong Vocational School) - Dewi, Rosmala; Sahono, Bambang; Risdianto, Eko; Muhaimin, Ahmad (IJOEM Indonesian Journal of E-learning and Multimedia, 2024)
This research aims to describe the development of Electrical Control Techniques Simulator-based learning media which can improve student learning achievement in the Electrical Power Installation Engineering subject and describe the effectiveness of developing Electrical Control Techniques Simulator-based learning media in improving student learning achievement in the Electrical Power Installation Engineering subject. In this research, R&D (Research and Development) design was used with the ADDIE model. The research subjects were class XI students majoring in Electrical Power Installation Engineering at Rejang Lebong State Vocational School. The data collection technique used is qualitative, namely collecting data by conducting observations, questionnaires and quantitatively by collecting pretest data before learning takes place and post-test after learning using learning media. Data analysis used average values and t-test. The validation instrument for material and media experts in research is the Likert scale. The results of the scale trial carried out on 60 students, consisting of 30 students (XI TITL2) in the control class and 30 students (XI TITL1) in the experimental class at SMKN 1 Rejang Lebong with the results of the post-test t test analysis showing sig (2-tailed) is 0.000, meaning the sig (2-tailed) is smaller than <0.05, meaning there is a significant difference between the experimental class and the control class. The conclusions of this research are: (1) The Electrical Control Techniques Simulator-based learning media developed is suitable for improving student learning achievement in the class XI Electrical Power Installation Engineering subject. (2) Development of Electrical Control Techniques Simulator-based learning media is effective in improving student learning achievement.